Investing in intrapreneurial capabilities for improved performance in state-owned enterprises - Lucy T. Chamba; Bobo Chazireni (Africa’s Public Service Delivery & Performance Review, 2023)
Background: State-owned enterprises (SOEs) are pivotal to the socio-economic development of any country. However, in most developing countries, these entities are failing to execute their mandate effectively. State-owned enterprises have failed to be responsive to citizens’ needs and deliver public value efficiently because of low investment in intrapreneurial activities by leadership in these entities.